THE INFLUENCE OF ANXIETY IN THE LIBRARY ON THE INFORMATION FULFILLMENT OF SDS IT AL-HIJRAH 2 DELI SERDANG SCHOOL USERS - Khalid Samahangga; Zahra Nabila Iqbal; Salniati Nasution; Muhammad Chaidir; Khalisatun Husna; Fajar Baihaqi (CV. Asry Persada Quality, 2024)
This research aims to investigate the impact of anxiety in the library on the information fulfillment of elementary school users at SD Sit Al Hijrah 2 Deli Serdang. The research focus covers three main aspects including academic anxiety, social anxiety, and environmental factors in libraries. The research results show that academic anxiety significantly influences library use by users. Apart from that, social anxiety also has an impact on library interactions with library staff. Environmental factors in libraries also contribute to the level of anxiety experienced by users. Furthermore, the use of technology in libraries can increase users' anxiety levels. The implications of these findings can help library managers in designing strategies to reduce user anxiety and increase comfort and effectiveness in using the library.